Detection of nitrogen substances by nuclear quadrupole resonance in large volumes - OKAY, CENGİZ (My University, 2023)
In this work, we describe the design of a sensing system for the NQR detection of nitrogen substances in a large inspection volume. The system consists of a Tecmag Scout NQR console, Tomco linear amplifier (4kW), a large distance/volume RF probe (either planar gradiometer or toroidal coil), a duplexer and a high-power Q-factor spoiler. We studied the conditions for optimal unilateral detection at distances up to 20 cm as well as for the detection inside a large volume. It has been shown that depending on RF probe configuration and ambient RF noise level), a 14N NQR signal of a small amount (100 g) of hexamethylenetetramine (HMT) as the reference nitrogen substance can be detected using both types of RF detectors. Furthermore, a possibility of NQR detection for a partially shielded HMT sample has been also shown. The influence of conducting bodies near an NQR sample for detection performance has been studied as well. We have also demonstrated that this system can be applied to the detection of ammonium nitrate.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Fizik; Atom ve Molekül Fiziği; Nükleer Fizik; Temel Bilimler; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Signal Processing; Physics; Atomic and Molecular Physics; Nuclear physics; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; TELEKOMÜNİKASYON; ALETLER & GÖSTERİM; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; NÜKLEER BİLİMİ VE TEKNOLOJİSİ; FİZİK, ATOMİK, MOLEKÜLER VE KİMYASAL; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; PHYSICS; TELECOMMUNICATIONS; INSTRUMENTS & INSTRUMENTATION; ENGINEERING, ELECTRICAL & ELECTRONIC; NUCLEAR SCIENCE & TECHNOLOGY; PHYSICS, ATOMIC, MOLECULAR & CHEMICAL; Bilgisayar Ağları ve İletişim; Fizik Bilimleri; Elektrik ve Elektronik Mühendisliği; Enstrümantasyon; Atom ve Moleküler Fizik ve Optik; Radyasyon; Computer Networks and Communications; Physical Sciences; Electrical and Electronic Engineering; Instrumentation; Atomic and Molecular Physics, and Optics; Radiation